PENGARUH PENGGUNAAN MODEL CONCEPT ATTAINMENT TERHADAP PEMAHAMAN KONSEP MATEMATIKA - Helma Mustika; Endang Sutriana (Universitas Islam Sumatera Utara, 2018)
Abstract. The purpose of this research is to know the understanding of mathematical concepts of students with the use of conceptual attainment model is better than the understanding of students' mathematical concepts with conventional learning. This research is quasi experimental research. The research design used was randomized subjects posttest only control group design. By selecting a Class VIII-2 sample as an experimental class and class VIII-1 as a control class of analytical techniques using the t-test as a hypothesis test, the prerequisite test is a normality test and homogeneity test. Based on the hypothesis test, t-test, obtained the price tarithmetic = 3.073 and price ttable = -1.997 at the real level of 0.05. Because tarithmetic ttable, so Ha accepted and H0 rejected. So it can be concluded that the ability to understand the concept of mathematics students using conceptual learning model attainment better than the ability to understand the concept of mathematics students using conventional learning model.Keywords: Concept Attainment, Understanding of Concept